Immunogenicity and Safety of Heterologous Versus Homologous Prime-Boost Regimens With BBIBP-CorV and Ad26.COV2.S COVID-19 Vaccines: A Multicentric, Randomized, Observer-Blinded Non-inferiority Trial in Madagascar and Mozambique - Ramgi, Patrícia; Siribie, Mohamadou; Rakotozandrindrainy, Njariharinjakamampionona; Bule, Odete; Shrivastava, Harshvardhan; Chambule, Lígia; Park, Eun Lyeong; Fernando, Carina; Boque, Jéssica; Macuiana, Rezelda; Razafimanantsoa, Ravomialisoa; Rakotozandrindrainy, Ndrainaharimira; et al. (Clinical infectious diseases, 2025)
Data on immunogenicity and safety of heterologous prime-boost (HePB) regimens using the BBIBP-CorV and Ad26.COV2.S have not yet been reported in sub-Saharan Africa.We conducted a randomized, observer-blinded, non-inferiority trial assessing the immunogenicity and safety of HePB regimens using BBIBP-CorV and Ad26.COV2.S, in adults aged 18-65 years. Participants enrolled, were stratified by baseline severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) serostatus, and randomized into four arms in a 1:1:1:1 ratio: A1 (BBIBP-CorV, Ad26.COV2.S), A2 (BBIBP-CorV, BBIBP-CorV), B1 (Ad26.COV2.S, BBIBP-CorV), and B2 (placebo, Ad26.COV2.S), administered at 28-day intervals. Fifteen participants in each arm were randomized separately in the immunology subset at a ratio of 1:1:1:1. Primary endpoints were the geometric mean titers (GMTs) of anti-SARS-CoV-2 neutralizing antibodies (nAbs) against SARS-CoV-2 Omicron variant BA.1 and safety at 4 weeks after second vaccination. The non-inferiority margin was 0.67 fold difference in geometric mean ratio (GMR) between the ratio of GMTs in the heterologous versus corresponding homologous arms.A total of 369 participants were randomized, and 367 of them received at least one dose of vaccine. Participants were between 18 and 65 years of age. Four weeks after second dose, GMT of nAbs in arms A1 and A2 was 802.7 (95% confidence interval [CI]: 635.3-1014.3) and 202.6 (95% CI: 150.8-272.1), respectively, with an adjusted GMR of 4.2 (2-sided 95% CI: 2.9-5.9). GMTs were 603.6 (95% CI: 446.1-816.7) and 725.7 (95% CI: 539.5-976.1) in arms B1 and B2, respectively, with an adjusted GMR of 0.8 (2-sided 95% CI: .5-1.2). Three serious adverse events were reported and none of them were related to the vaccination.The noninferiority criterion was met only in arm A1 versus A2. HePB regimens were safe and well tolerated.NCT04998240.
Online verfügbar: 22. Juli 2025
Gesehen am 16.12.2025